Pengaruh Intensitas Mengakses Konten Spiritual pada Aplikasi TikTok terhadap Tingkat Religiusitas Mahasiswa Prodi PAI UIN Palangka Raya - Ridma Azizah Putri; Ajahari Ajahari; Abdul Gofur (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of the intensity of accessing spiritual content on the TikTok application on the religiosity level of students in the Islamic Education Study Program (PAI) at UIN Palangka Raya. Using a quantitative approach with a survey method involving 80 students, data were collected through a Google Form questionnaire. The results of a simple linear regression test showed a positive and significant effect between the intensity of accessing spiritual content and the students’ religiosity level. The regression coefficient was 0.984, and the t-value was 6.105, which is greater than the t-table value of 2.239 with a significance level of 0.000 < 0.05. This indicates that the higher the intensity of accessing spiritual content, the higher the level of student religiosity. The study concludes that spiritual content on TikTok can be an effective medium of da’wah to enhance students' religiosity, especially within religious education settings.